Komparatif Efektivitas Model Problem Based Learning Berbantuan Media Diagram Pintar (DIPIN) dan Pembelajaran Konvensional Terhadap Kemampuan Pemahaman Konsep Matematika Siswa Kelas 5 SD - Sari, Duwike Wulan; Putri, Audita Nelisa; Lestari, Indah Puji; Aulia, Nadhira Agfifaza; Amaliyah, Fitriyah (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study aims to examine the effectiveness of the Problem-Based Learning (PBL) model assisted by DiPin media on students' conceptual understanding in the topic of data collection. The research employed a quantitative method with a quasi-experimental design involving two classes at SD Tanwirul Qulub Kudus: class 5A as the experimental group using the PBL model assisted by media, and class 5B as the control group using only the conventional model. The instruments used were pre-test and post-test questions designed to measure students' mathematical conceptual understanding. Data analysis was conducted using five statistical tests: normality test, homogeneity test, ANOVA, Paired Sample t-Test, N-Gain, and Independent Samples t-Test. The results showed that learning with visual aids was more effective in improving students’ conceptual understanding and numerical abilities compared to conventional learning. The test data from classes 5A and 5B were normally distributed (p > 0.05) and had homogeneous variances (p = 0.411), fulfilling the requirements for parametric testing. The ANOVA test showed a significant difference between the two classes (p = 0.000; F = 31.370). In class 5A, the Paired Sample t-Test indicated a significant increase from pre-test to post-test (a 25-point increase; p = 0.000). The N-Gain score in class 5A was also higher (63.79%) compared to class 5B (23.51%). The Independent Samples t-Test confirmed these findings with significant results (p = 0.000), and the average post-test score was higher in class 5A (84.67) compared to 5B (65.67). Thus, learning using visual aids has been proven to be more effective in improving student learning outcomes.